Hydrazine-Containing Heterocycle Cytochalasan Derivatives From Hydrazinolysis of Extracts of a Desert Soil-Derived Fungus Chaetomium madrasense 375 - Guo, Qingfeng; Chen, Jinhua; Ren, Yuwei; Yin, Zhenhua; Zhang, Juanjuan; Yang, Baocheng; Wang, Xuewei; Yin, Wenbing; Zhang, Wancun; Ding, Gang; Chen, Lin (Frontiers in Chemistry, 2021)
“Diversity-enhanced extracts” is an effective method to produce chemical libraries for the purpose of drug discovery. Three rare new cytochalasans derivatives chaetoglobosins B1-B3 (1-3) were obtained from chemically engineered crude broth extracts of Chaetomium madrasense 375 prepared by reacting with hydrazine monohydrate, and four known metabolites chaetoglobosins (4-7) were also identified from the fungus. Their structures were identified by NMR and MS analysis and electronic circular dichroism simulation. In addition, the antiproliferative activities of these compounds were also evaluated, and the drug-resistant activities of cytochalasans were evaluated for the first time. Compound 6 possessed potent activity against four human cancer cells (A549, HCC827, SW620, and MDA-MB-231), and two drug-resistant HCC827 cells (Gefitinib-resistant, Osimertinib-resistant) compared with the positive controls.